At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

Simplify this expression.
(√2+√3)(√5-√7)
O √5+√=2
O √10+√15-√14-√21
02√5-2√7
O 2√5 +3√5-2√7-3√7


Sagot :

199932

[tex] \sqrt{10} - \sqrt{14} + \sqrt{15} - \sqrt{21} [/tex]

The answer is B

Answer:

√10+√15-√14-√21

Explanation:

(√2 * √5) = √10

(√2 * -√7) = -√14

(√3 * √5) = √15

(√3 * -√7) = -√21

Put it all together: √10 + √15 - √14 - √21

Hope this helped :)